Usulan Perbaikan Tata Letak Fasilitas Pada Area Produksi Menggunakan Metode From to Chart (Studi Kasus: PT. Ibrahim Bin Manrapi) - Muhammad Ivan Yudha Rifdhani; Hidayat Hidayat; Akhmad Wasiur Rizqi (Jurnal Serambi Engineering, 2023)
An industry, both in the help and assembling areas, unquestionably has a few offices to help its creation cycle. Office design connects with the area, format, floor plan, equipment, and exercises related with the work environment. Different sorts of data from research led by finishing direct discernments and assessments made by areas on organizations taking part in the assembling of woven sarong materials at PT. Ibrahim Bin Manrapi which is situated on Jl. Malik Ibrahim Gresik, 24-26. in view of the discoveries of the examination of PT. In terms of format prior to design planning, PT. Ibrahim Bin Manrapi 's container is that there are still many areas that are not utilized to their full potential, and there are still many distances between offices that must be expanded as much as possible. From the technique for making the stream before the platform, there is a material conveyance distance of 102 m. Given the effect of information the board from the issues seen by PT. Ibrahim Bin Manrapi saw a lack in the plan so the gathering cycle went poorly and the conveyed item couldn't be anticipated to be great. This course of action should be possible by arranging the arrangement of the assembling office utilizing the From To Chart (FTC) procedure to restrict forward and backward during the assembling cooperation (Backtracking).